Instructional Design for SDG 4: Developing Collaboration Skills Through an ADDIE-Based Peer Project Learning Model - Paulina Maria Ekasari Wahyuningrum; Siti Masitoh; Andi Kristanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop the Peer Project Collaborative Learning (PPCL) model and examine its feasibility, practicality, and effectiveness in improving junior secondary students' critical thinking and collaboration skills in Catholic Religious Education at St. Paulus Catholic Junior High School, Palangka Raya. Method: This study employed a Research and Development (R&D) approach using the ADDIE framework (Analyze, Design, Development, Implementation, and Evaluation). statistics, normalized gain analysis, and an independent-samples t-test. Results: The findings indicate that the PPCL model achieved a very high level of validity based on expert judgment (98.8%) and demonstrated high practicality through positive responses from teachers and students (91%). The pretest results showed no significant difference between the experimental and control groups (p = 0.534), confirming comparable initial abilities. Following implementation, students who learned through the PPCL model achieved significantly higher collaboration performance than those receiving conventional Project-Based Learning (M = 41.26 vs. 38.26; t(66) = −6.241, p < 0.001), with a higher normalized gain (0.60 vs. 0.44). Novelty: The findings extend constructivist and collaborative learning theories by demonstrating that structured reciprocal peer interaction embedded within collaborative project activities effectively reduces free-riding, promotes active participation, and enhances twenty-first-century competencies. The PPCL model also offers practical guidance for teachers seeking to design student-centered learning environments that strengthen both cognitive and collaborative competencies in religious education and other secondary school contexts for SDG 4.